G564(P) Pilot interventions to improve hba1c within a paediatric diabetes service; a quality improvement initiative. (May 2019) - Khetriwal, B; Dekyem, P; Durso, A; Brown, J; Shah-Enderby, K; Vinter, K
Abstract : Aim: The outlined project arose from the participation of the current paediatric diabetes team within the RCPCH Quality Improvement initiative for Paediatric Diabetes teams in England. The team aimed to reduce mean and median HbA1c of their patient group (n=120) and to improve patient satisfaction with the service Method: The team attended regular RCPCH QI meetings (from November 2017 – July 2018) and focused on Plan-Do-Study-Act (PDSA) cycles to analyse the effectiveness of a number of pilot interventions, in line with the above aims. Baseline and follow-up feedback on satisfaction with the service was gathered from patients. Baseline data suggested that improvements needed to be made in patient education, patient empowerment and ensuring adherence to clinic appointment times. A number of initiatives were trialled. These included: giving patients topic choices to discuss in clinics (as requested by patients), introducing 'time reminders' to consultants conducting the clinic and changing the format of annual reviews to ensure the recommended key care processes were completed within a timely manner. Diasend workshops were also implemented in order to encourage patients to review and monitor trends in their blood glucose levels between clinic appointments. The team met weekly to ensure the above initiatives were delivered in a clear, coherent and consistent way. Results: Since initiating these changes, the clinic median HbA1c for the current patient group has dropped from 67.0 (November 2017) to 60.0 mmol/mol (August 2018), constituting a 10% reduction in median HbA1c within the space of 8 months (see Figure 1). The percentage of patients with an HbA1C of 70 mmol/mol or higher (i.e. those at risk of both acute and long term diabetes-related complications) has reduced from 49 to 23 percent (see Figure 2). On-going feedback from patients also suggests improvements in satisfaction with the service. Conclusion: The project was successful in achieving the outlined aim of improving mean and median HbA1c for the current patient group and improving patient satisfaction with the service. Further PDSA cycles with new initiatives will continue to be implemented with the purpose of continuing the improvements observed.